SPECIFIC FEATURES OF DYNAMICS OF TWO-MODE COURSE INDICATORS - Ryzhkov , L. M.; Ivanov , S. V. (Problems of Informatization and Management, 2021)
The dynamics of an adjustable gyrocompass (CGC) as a dual-mode heading indicator with automatic change of the operating mode is analyzed. It is shown that by switching the device to the gyro-azimuth mode, it is possible to provide high accuracy of readings. The operation of the device with the use of an observing device connected for the period of maneuvering is considered.